2011
DOI: 10.1097/pcc.0b013e3181e3250c
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis in neonates undergoing the hybrid approach to complex congenital heart disease*

Abstract: The prevalence of NEC in patients undergoing the hybrid procedure is comparable to that reported for neonates undergoing the Norwood procedure. Earlier gestational age is a significant risk factor for NEC in patients who undergo the hybrid Stage I procedure. Multidisciplinary approaches to better understand abdominal complications and to develop feeding regimens in neonates undergoing the hybrid approach to complex CHD are needed to improve outcomes and decrease morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 26 publications
5
39
2
Order By: Relevance
“…One alternative palliative procedure for these patients is the hybrid procedure, consisting of bilateral pulmonary artery banding, patent ductus arteriosus (PDA) stenting, and balloon atrial septostomy . We previously reported that the incidence of NEC in patients undergoing the hybrid procedure was 11% . Lower gestational age and lower prostaglandin dosage were the only risk factors found in patients who developed NEC after the hybrid procedure.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative palliative procedure for these patients is the hybrid procedure, consisting of bilateral pulmonary artery banding, patent ductus arteriosus (PDA) stenting, and balloon atrial septostomy . We previously reported that the incidence of NEC in patients undergoing the hybrid procedure was 11% . Lower gestational age and lower prostaglandin dosage were the only risk factors found in patients who developed NEC after the hybrid procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of NEC is high in neonates with congenital heart disease, especially in those patients with single ventricle physiology . The immediate short‐term outcomes have been described, but less is known about mid‐term outcomes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Since bypass times were not different between groups, this would suggest that at least some of the technical aspects of the surgery were not major contributing factors in the development of NEC. It must also be added that since NEC occurs in patients undergoing the hybrid procedure as well, which does not require cardiopulmonary bypass, it may be the overall underlying physiology of a circuit in parallel versus series that places these patients at increased risk for NEC and not just the fact of undergoing cardiopulmonary bypass . The ability to accurately determine the presence of residual lesions after the surgical procedure and decisions to intervene or not intervene were difficult to ascertain from the database, so no comment was made on those issues to determine if there were differences in those variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations